DINAMIKA PEMBELAJARAN DARING MATA PELAJARAN AQIDAH AKHLAK DI TENGAH PANDEMI COVID-19 DI MI MUHAMMADIYAH 19 SIDOKUMPUL: DINAMIKA PEMBELAJARAN DARING MATA PELAJARAN AQIDAH AKHLAK DI TENGAH PANDEMI COVID-19 DI MI MUHAMMADIYAH 19 SIDOKUMPUL - Zakhiru Rahma Zaha; Umi Rosyidah; Zunaidah (STAI Muhammadiyah Paciran Lamongan, 2023)
Indonesia is currently faced with challenges in the midst of the Covid-19 pandemic, where the government urges the Indonesian people to stay at home. The Covid-19 pandemic does not only affect the economic and social sectors, but also the education sector which must now begin to adapt to this era. The purpose of the research in writing this articel is to determine the online learning process at MI Muhammadiyah 19 Sidokumpul, to find out the problems of online learning at MI Muhammadiyah 19 Sidokumpul, and to find out what efforts or solutions are being made to solve learning problems. online for fifth grade students at MI Muhammadiyah 19 Sidokumpul. This study uses a descriptive qualitative research approach Data collection is done by means of observation, interviews, and documentation. Data analysis techniques used are data collection, data reduction, and data verification. The results showed that online learning at MI Muhammadiyah 19 Sidokumpul experienced several problems, namely: (1) Problems related to students who feel bored and bored. (2) The problem of differences in the level of understanding of students. (3) The problem of parents who do not have android. (4) Lack of cooperation between parents and students.